The Continued Absence of the LGBTIQA Community in School History Textbooks in Post-Apartheid South Africa (Yesterday & Today Journal for History Education in South Africa and abroad, 2024)
School history textbooks in South Africa are essential teaching and learning materials for most history teachers and learners, because they are often the only materials used to engage with the past. These textbooks are also considered to contribute to the construction of an ideal citizenry, as well as fostering national identity, unity, and reconciliation (Bertram and Wassermann 2015; Bam, Ntsebeza and Zinn 2018). However, our concern is that while textbooks appear to be used to construct an ideal citizenry who is supposed to have reconciled and united into one national identity, there also appears to be a concerted effort to exclude, within both the written and visual texts of the textbooks, those South Africans who identify as Lesbian, Gay, Bisexual, Transgender, Intersex, Queer/Questioning, Asexual, and many other identities (LGBTIQA+). Through abyssal and post-abyssal epistemology as our theoretical frameworks, and critical discourse analysis as our tool of analysis we were able to investigate how four history textbooks across four grades within the Senior and Further Education and Training phase that we purposively and conveniently sampled continue to exclude LGBTIQA+ contributions and experiences within the knowledge base of the school history curriculum, despite the pivotal role some played during the struggle against apartheid. We have since concluded that the erasure of the LGBTIQA+ community amounts to another dehumanising act against this group of people that is epistemic, existential, and ontological in nature. We also argue that this act denies all history teachers and learners, irrespective of their sexual orientations, the opportunity to engage with diverse historical contributions and experiences of all South Africans.
Keywords: Abyssal Epistemology; History textbooks; HMTT; LGBTIQA+; South Africa; School history